Volatility of publicly-listed corporations' stock prices to IFRS prescription of fair value accounting from 2001 to 2013 - Paril, Alloysius Joshua S. (Animo Repository, 2015)
The adoption of the International Financial Reporting Standards (IFRS) could probably be one of the most important milestones in the history of financial reporting. As of this writing, more than 100 countries have already switched from their local generally accepted accounting principles (GAAP) to the IFRS. And the Philippines joined the bandwagon in 2005. But the IFRS is not without issues. Since it was adopted by the Philippines in 2005, a number of changes have been made and implemented: new treatments on certain items, deletion and replacements of particular requirements, even the implementation of new standards. And one of the most controversial characteristics of the IFRS is its prescription to report certain accounts in the financial statements at fair value. Up until now, this particular requirement by the standard setters has yet to have unequivocal support. But still, it seems to be assumed by the IFRS that fair value does really have an effect on the financial statements, and ultimately the decisions of the financial statement users. This study aims to confirm or refute just that. By taking a look at the association between the book value and market value of the stocks of publicly-listed companies in the Philippines as represented by Tobin's q, and by determining which accounts that can be presented at fair value significantly influences the stock price of a company, I aim to achieve if such assumption is appropriate.